Acculturation: Its influence on the cultural practices of Manobo learners of Bukidnon - Pico, Erl Gerome; Gallego, Mary Grace (Journal of Social, Humanity, and Education, 2025)
Purpose: This study aimed to assess the extent of acculturation and its relationship with the cultural practices of Manobo learners in Damulog, Bukidnon, focusing on assimilation, integration, and marginalization. Research methodology: A descriptive and correlational research design was used. The study utilized a researcher-made survey questionnaire administered to 300 Grade 10 Manobo learners across four secondary schools in the Damulog area of Bukidnon. The data were analyzed using descriptive and inferential statistics. Results: The study revealed that Manobo learners often experience acculturation in terms of assimilation, integration, and marginalization. Their cultural practices in the economic, social, political, and spiritual aspects were also evident. A moderate positive relationship was found between the extent of acculturation and the level of cultural practices among the learners, suggesting that higher levels of acculturation are associated with stronger cultural practices. These findings imply that acculturation influences how Manobo learners maintain their cultural heritage while adapting to new societal influences. Conclusions: Indonesia’s BRICS membership can bolster national defence and strategic autonomy if managed with diplomatic prudence. A balanced foreign policy is essential to leverage the advantages of BRICS while preserving partnerships with Western powers and the ASEAN allies. Investment in cybersecurity, military modernization, and defence diplomacy is crucial for long-term stability. Limitations: This study is limited to Grade 10 Manobo learners in Damulog, Bukidnon, and may not represent other Indigenous groups or age levels. Self-reported data may also introduce bias, and external factors, such as socioeconomic background, were not fully examined. Contribution: This study contributes to the understanding of how acculturation impacts the cultural practices of Indigenous learners, particularly in educational settings.